Factors Affecting Coffee Seed Farming Production (Coffea arabica L.) and Its Implications for Income - Febriyanto, Riyan; Sukmawati, Dety; Gantini, Tuti (Journal of Innovation and Research in Agriculture, 2024)
ABSTRACT Coffee seed is one of the forest products with a lengthy marketing chain, in which numerous marketing agencies are involved; therefore, there is a need to improve efficiency in order to increase the value of existing coffee seed cultivation. It is regarded necessary to conduct research with the title "Factors Affecting Production of Arabica Coffee Seed Farming and Their Financial Implications." Farmers always anticipate high profits from their agricultural productions. To maximize profits, farmers and breeders must increase production and decrease production costs. Therefore, producers must be able to efficiently provide agricultural inputs on agricultural land. Not necessarily does the availability of agricultural inputs result in high productivity. Large income does not always indicate high efficiency, so efficiency measurements should follow the analysis of income. This study's target population consisted of Arabica coffee cultivators in Cianjur Regency. There are 30 individuals who propagate or sell Arabica coffee seeds. On the basis of the outcomes of field data analysis and hypothesis testing, as well as the discussion, the following research conclusions can be drawn: The performance of Arabica coffee seed cultivation in the Cianjur Regency is characterized by the use of leased land and an average business size of 7,700 stems. The required investment ranges between 2 and 8 million IDR. The seed mortality rate is approximately 22%, and the resulting products are separated into three grades: grade 1, 39.17%, grade 2, 35.87%, and grade three, 25%. The nature of the farmer's primary commercial enterprise is a source of support for the farmer's domestic economy. Seed inputs are acquired independently, and occasionally in collaboration with seed entrepreneurs from outside the city. Arabica coffee seed cultivation generates an average seasonal income of IDR 12,928,150 with a business efficiency rating of R/C 2.